Impaired meningeal lymphatic drainage in Listeria monocytogenes infection - Feng, Jian; Ren, Yuanzhen; Wang, Xilin; Li, Xiaojing; Zhu, Xingguo; Zhang, Baokai; Zhao, Qi; Sun, Xiaochen; Tian, Xinxin; Liu, Hongyang; Dong, Fan; Li, Xiu-Li; et al. (Frontiers in Immunology, 2024)
Previous studies have demonstrated an association between lymphatic vessels and diseases caused by bacterial infections. Listeria monocytogenes (LM) bacterial infection can be life-threatening and affect multiple organs, such as the brain, intestine, liver, spleen, and lung. However, the impact of LM infection on morphological and functional changes of lymphatic vessels remain unexplored. In this study, we found that LM infection leads to the expansion of meningeal lymphatic vessels (MLVs) and mesenteric lymphatic vessels in mice, but also impairs MLVs-mediated macromolecules drainage. Interestingly, we found that the genes associated with lymphatic vessel development and function, such as Gata2 and Foxc2, were downregulated, suggesting that LM infection may affect cellular polarization and valve development. On the other hand, photodynamic ablation of MLVs exacerbated inflammation and bacterial load in the brain of mice with LM infection. Overall, our findings indicate that LM infection induces lymphangiogenesis and may affect cell polarization, cavity formation, and valve development during lymphangiogenesis, ultimately impairing MLVs drainage.